Sequência didática para ensino de conceitos sobre medidas de tempo para crianças surdas - Rosalen, Josiani Israel (2019)
The main objective of this work is propose a Didactic Sequence (DS) for the teaching concepts related to measurement and temporal representation for deaf students and evaluate the contributions of the use of this material in teaching concepts related to the theme. The target audience are deaf students participating in the Specialized Educational Service from the Training Center for Professionals of Education and Assistance to People with Deafness and enrolled in the Municipal Public Schools of Cascavel / Paraná. The developed DS uses manipulative materials to address Time Measures, more specifically, the recording and passage of time. The activities were designed aiming to the teacher take advantage of the students' previous knowledge to guide the actions of future activities. In terms of teaching, DS aims to assist students in understanding the passage of time, highlighting the periods present in the day and their influence on the life and organization of people's daily activities. The material produced aims the active participation of students in order to simulate situations that occur to them daily. The materials were thought respecting the deaf culture, being organized in a visual and participative way. The main source of data collection was the filming performance of the students in doing the activities. The contributions of the proposed DS to the teaching of this theme to deaf students were grouped into five analysis dimensions proposed from emerging indicators of the teacher's observations during the application of DS and the students' performance to perform the proposed tasks in each activity. they: (i) student's attitude towards the activity; (ii) Notion of Past, Present and Future; (iii) contrast Hours x Time of day; (iv) Identification / representation of hours on the clock and (v) Curriculum Activities x Daily activity. Considering the data analysis based on the analysis dimensions, we believe that the objectives of this research were achieved.